An evaluation of adherence to folic acid supplementation in pregnant women during early gestation for the prevention of neural tube defects. Issue 11 (25th November 2022) - Linnell, Anna; Murphy, Niamh; Godwin, Jon; Cremona, Alexandra
Abstract: Objective: Neural tube defects (NTD) are potentially preventable by periconceptual folic acid supplementation. Women with obesity are at higher risk of NTD, therefore, are recommended a higher dose of 5 mg folic acid to mitigate this risk. The aim of this study was to evaluate maternal practice of folic acid supplementation amongst the antenatal population in relation to maternal obesity status. Design: Prospective observational study. Setting: Women ≤18 weeks' gestation at their first antenatal appointment attending University Maternity Hospital Limerick (Ireland) were recruited. Maternal height and weight were measured. Obesity was defined at a threshold of ≥30·0 kg/m 2 and ≥27·5 kg/m 2 when adjusting for ethnicity. A two-part questionnaire captured maternal characteristics and assessed supplementation compliance, commencement and dosage. Fisher's exact test for independence analysed differences in variables. A P value of <0·05 was considered significant. Participants: A total of 328 women participated over a duration of 6 weeks. Results: Mean gestational age was 12·4 ± 1·4 weeks and mean BMI 26·7 kg/m 2 ± 5·2 kg/m 2 . 23·8 % ( n 78) were classified as obese. 96·5 % ( n 315) were taking folic acid and 95·7 % ( n 314) supplemented daily. 30·2 % ( n 99) commenced supplementation 12 weeks prior to conception. Overall, 57·9 % ( n 190) of women met folic acid supplementation dose requirements. 89·1 % ( n 55) of women with obesity did not. Women with obesity were less likely to meet the higher folic acid supplementation dose requirements ( P =< 0·001). Conclusion: Folic acid supplementation practices within this cohort were suboptimal to prevent their risk of NTD. This study showed inadequate compliance of folic acid supplementation, and inadequate dosage for women with obesity. Increased patient education and awareness are needed within the antenatal period of pregnancy to bring folic acid supplementation practices in line with best practice guidelines.